Nickel Alloying Significantly Enhances the Power Density of Ruthenium‐Based Supercapacitors. Issue 9 (8th July 2020) - Morag, Ahiud; Shauloff, Nitzan; Maman, Nitzan; Froumin, Natalya; Ezersky, Vladimir; Jelinek, Raz
Abstract: Supercapacitors operating at high frequencies while exhibiting high capacitance have been challenging to fabricate due to high resistance and constrained ion diffusion in the active layers. To overcome these limitations, thin layers of pseudocapacitive materials with high theoretical capacitance can be used. Still, construction of such electrodes exhibiting effective ion diffusion, sufficient electrochemically‐active surface area, and high conductivity has encountered significant difficulties. Here, we integrated nickel atoms into a ruthenium layer through a simple electrochemical deposition method, producing a thin electrode comprising hexagonal nickel ruthenium (NiRu) nanodendrites. Further oxidation of the NiRu alloy generated a thin surface layer of pseudocapacitive RuO2 exhibiting significant areal capacitance. A symmetric device from two NiRu/RuO2 electrodes displayed an energy density of 0.714 μWh cm −2 with a remarkable power density of 1500 mW cm −2, ∼250 W cm −3 for a full device. The NiRu/RuO2 supercapacitor outperforms commercial capacitors in both energy and power densities and may replace bulky capacitors in microelectronic devices. Abstract : The role of Ni : The power density of supercapacitors is limited both by charge resistance and ion diffusion in the active layer. Here, we show that incorporation of nickel into a ruthenium layer significantly enhances the electrochemical performance. More than 2‐fold increase in the power density of the NiRu‐based device compared to the bare Ru device was achieved, exhibiting power density of 1500 W cm −2 and over 250 W cm −3 for a full device.